Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s10798-015-9305-4
|View full text |Cite
|
Sign up to set email alerts
|

What preconceptions and attitudes about engineering are prevalent amongst upper secondary school pupils? An international study

Abstract: In the Netherlands, as well as in many other countries, there is an increasing interest in implementing education about engineering as a part of general education at the upper secondary school level. In order to know what pupils at that level think about engineering, a study has been done to investigate their attitude towards and their concept of engineering. This study was done not only in the Netherlands but also in 39 other countries. In the preparation of the study, pupils were asked to draw concept maps o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 5 publications
(5 reference statements)
1
10
0
Order By: Relevance
“…Students viewed doing research activities as more relevant and important to know about than designing. The positive attitude found towards doing design activities is similar to findings on students' positive attitudes towards engineering (Ara et al, 2011;Kőycű & Vries, 2016), which is, like designing, another technology and science related activity. It should be noted, however, that while they have similar translations in Dutch, this may not be the case for all languages or cultures, and therefore designing and engineering cannot be regarded as exactly the same.…”
Section: General Attitudes Of Secondary School Students Towards Doingsupporting
confidence: 81%
See 1 more Smart Citation
“…Students viewed doing research activities as more relevant and important to know about than designing. The positive attitude found towards doing design activities is similar to findings on students' positive attitudes towards engineering (Ara et al, 2011;Kőycű & Vries, 2016), which is, like designing, another technology and science related activity. It should be noted, however, that while they have similar translations in Dutch, this may not be the case for all languages or cultures, and therefore designing and engineering cannot be regarded as exactly the same.…”
Section: General Attitudes Of Secondary School Students Towards Doingsupporting
confidence: 81%
“…Another study found that technology-oriented company visits for primary school children also did not lead to an increased positive attitude towards technology (Post & Walma van der Molen, 2014). Students' attitudes towards design and engineering on the other hand, tend to be fairly positive (Ara et al, 2011;Kőycű & Vries, 2016). This could indicate that students hold different attitudes towards the abstract topics of technology or science, compared to doing technology or science related activities (like engineering and doing research).…”
Section: Attitudes Towards Doing Research and Design Activitiesmentioning
confidence: 99%
“…More than 65% of the students also stated that technology is more than just objects; it has to do with knowledge and/or activities as well (Mitcham Score ≥ 2). Yes, technological objects is the most common way to describe technology in this study as well as being mentioned in previous research (Burns 1992;DiGironimo 2011;Garmire and Pearson 2006;de Vries 2006;Kőycű and de Vries 2015;Riis and Augustsson 1991). However, we must emphasize the fact that a majority of the students in this study describe technology in a broader way than as technological objects.…”
Section: Discussionmentioning
confidence: 53%
“…To a large extent, this negatively affects their pursuit of engineering-related majors and careers and the development of engineers in society (Hayden et al, 2011;Kutnick et al, 2017;UNESCO, 2010). A review of the literature also shows that the majority of studies has focused on exploring students' attitudes toward engineering and STEM subjects (de Vries, 2016;Unlu, 2016). However, few studies have explored the factors underlying students' attitudes towards engineering by investigating their participation in engineering practice at the secondary level in Shanghai, China.…”
Section: Introductionmentioning
confidence: 99%